Characterization of Gemstones Using Nanoparticle Enhanced Laser Induced Breakdown Spectroscopy (NELIBS) - Eng, Wei Hang; Syed Zuhaib Haider Rizvi (Enhanced Knowledge in Sciences and Technology, 2024)
Gemstone characterization is an important aspect of gemology and requires precise analytical techniques. Laser-Induced Breakdown Spectroscopy (LIBS) has shown its ability to analyze multiple elements rapidly with a single shot of laser using atomic emission principles. However, Laser-Induced Breakdown Spectroscopy (LIBS) has its own drawback in characterizing gemstones due to their high refractive index, causing inefficient ablation, crack formation, and limitations in detecting trace elements and complex compounds. This research is mainly aimed to enhance the signal of emission spectrum as well as compare the damage induced by Nanoparticle Enhanced Laser Induced Breakdown Spectroscopy (NELIBS). This study involved the deposition of gold (Au NPs) nanoparticles onto samples of Blue Sapphire and Opal gemstones using a micropipette and analyzing them with LIBS using a pulsed Nd:YAG laser and HR4000+ spectrometer with the help of Spectrasuite software. The research conducted has demonstrates the enhancement of the laser energy absorption on the sample. This enhancement can be explained by an increase in signal intensity as well as the enhanced spectral emissions. NELIBS has demonstrated its ability to prevent direct interaction between intense laser pulses and gemstones, thus reducing the laser-induced damage to the sample. This also leads to enhanced plasma formation and radiation emission, thereby enhancing the accuracy and sensitivity for gemstone analysis.